Wood Anatomy of Indian Flacourtiaceae - Chauhan, Laxmi; Raturi, R. D.; Rao, R. V.; Dayal, R. (Indian Forester, 1995)
Wood Anatomy of 8 genera of Indian Flacourtiaceae has been described in detail. The study indicates that type of ray-vessel pitting and perforation plate are of diagnostic value in separating the genera Hydnocarpus and Gynocardia. The remaining genera have more or less similar anatomical features. However the important anatomical features have been tabulated for facilitating specific identification.